Implementing technological change with cross-functional teams Robert A. Lutz explains how Chrysler erases the line between innovators and implementers - Lutz, Robert A.
Chrysler management strives to erase the line between the people who innovate and the people who implement.
In an effort to produce quality products more quickly and at less cost, Chrysler Corporation has instituted a cross-functional system of platform teams within the organization. Many facets of the organization, including R&D, now benefit from being more directly involved in the production process. Whereas in the past, departments worked as separate entities, specialists from each now come together to work more efficiently within one of the four major platform teams. And, with the success of their new products, Chrysler realizes that limited resources-if focused and organized-do not necessarily have to be a liability. By bridging the gap between those who invent and those who implement, Chrysler is emphasizing the spirit of teamwork along all stages of product development and technological change.
Keywords: Technological change; Cross-functional teams